ANTIBACTERIAL AND SYNERGISTIC ACTIVITY OF TERMINALIA CHEBULA AND TERMINALIA BELLERICA FRUIT EXTRACTS AGAINST ESBL PRODUCERS - Thirunavukkarasu, Bharani; Purushothaman, Nirmala (International Journal of Current Pharmaceutical Research, 2017)
Objective: Bacterial infections and the resistance related to indiscriminate antibiotic use have led to an alarming situation in the clinics. The rapid spread of Extended Spectrum Beta Lactamases (ESBLs) and carbapenemase producing Gram negative bacteria has initiated the need for development of a new drug or an alternative choice by using the combination of drugs with medicinal plant extracts. This study was aimed at examining the antibacterial potential and synergistic activity of ethanolic extracts of Terminalia chebula and Terminalia bellerica fruits against clinically important reference bacterial strains. Methods: The crude ethanolic extracts of T. chebula and T. bellerica fruits were prepared and reconstituted with 5% dimethylsulfoxide (DMSO). The fruit extracts (~25 mg/well) were added into the wells in the plates inoculated with various ESBL and AmpC producers and they were incubated at 37 °C for 24 h. The antibiotics ceftazidime (30 µg) and cefotaxime (30 µg) were added to the wells alone and in combination with the fruit extracts to determine their own antibacterial and synergistic activity respectively. Results: The ethanolic fruit extracts combination improved the activity of ceftazidime and cefotaxime against the tested ESBL and AmpC producers. Though both the extracts showed activity, T. chebula was found to show better synergistic antibacterial activity. Conclusion: The synergistic activity of these fruit extracts with ceftazidime and cefotaxime against the ESBL and AmpC producers shows the efficiency of the combination therapy, which can be considered in therapeutic point of view to prevent the misuse of antibiotics and minimise the increasing resistance in bacteria.